A comparison between therapeutic effects of Salvia Officinalis. Extract, meloxicam and dexamethasone following acute sciatic nerve injury due to analgesic drug injection in rats - Mahdieh Katebian; Mirsepehr Pedram; Mohammadmehdi Dehghan; Korosh Mansoori; Mahya Lalehpoor; Farid Kosarifard (Elsevier, 2023)
Background: An intramuscular (IM) injection into gluteal muscle can lead to iatrogenic trauma to sciatic nerve. The drugs can be injected directly into sciatic or into the tissue adjacent to the nerve. Besides the direct damage to nerve due to needle and drug entrance to nerve tissue, the chemical nature of each drug activates immune system near healthy peripheral nerves in order to remove damaged tissues and start healing process. This immune system response has a great role in creating pathological pain and it makes functional recovery as a major challenge. Material method: In this study, 25 adults male Fischer- Wistar rats were used. An analgesic drug (diclofenac) was injected in the muscles near sciatic nerve (4 groups) and also in sciatic nerve (1 group, nerve control group). For clinical assessment of sciatic nerves integrity, sciatic functional index test (SFI test) was done before, 1 day and 7 days after surgery. Treatments with meloxicam, dexamethasone and extract of Salvia Officinalis were started for 3 muscle groups and 1 group remained as a control muscle group. After 1 week, all the animals were euthanized under deep anesthesia and the sciatic nerves with surrounding muscles were removed and sent to histopathological examination. Results: all three treatment groups showed decreased inflammatory process and increased repair regeneration in compare to control group. Although, the amount recovery in the dexamethasone group was significantly higher in compared to the control and other treatment groups. Conclusion: This study showed That IM injection of analgesic drug (Diclofenac), without direct damage to sciatic nerve, causes activation of the immune system and iatrogenic sciatic neuropathy. This study also showed therapeutic effects of two common drugs (NSAID and corticosteroids) and an extract of Salvia Officinalis. Treatment with all three drugs, decreased inflammatory response at injury site and increased recovery but Long-term usage of corticosteroids and NSAIDs can be challenging. The Salvia extract also have showed acceptable improvement effects with minimal side effects.